Respuesta del cultivo de maní (arachis hipogea l.) a dos métodos de riego a presión en el valle de casanga, provincia de Loja - Torres Sarango, Italo Alexander (2016)
Thesis project entitled: "RESPONSE OF THE CULTIVATION OF PEANUTS (Arachis Hipogea L.) TWO METHODS OF IRRIGATION TO PRESSURE IN THE VALLEY OF CASANGA, PROVINCE OF LOJA" was held in the canton avocados, province of Loja, in view that its inhabitants since ancient times grown peanuts as one of the main products, however by the low rainfall in this territory have been lost up to 70% of the production, which has motivated to conduct this research compare two most common pressurized irrigation methods in the Middle as It is the method of drip irrigation and spray, compared in turn with the irrigation by furrows, same that was performed based on the following objectives: to determine the efficiency of two irrigation methods (sprinkler and drip) pressure in the Valley of Casanga; Evaluate economic, financial, and environmentally two pressurized irrigation methods (sprinkler and drip, comparing quantity and quality), the cultivation of peanuts; calibrating technology of evaporimeter tank type 'A' versus a tank evaporimeter craft. The purpose of the research was to determine productivity and costs of production between witness and pressurized irrigation methods to determine irrigation technology is suitable to apply it in the Valley of Casanga. For each treatment were three repetitions, while the variables measured at the stage of field cultivation were: number of branches per plant within 80 days from sowing, height of the plant to 90 days, number of pods per plant, sheath length, weight 10 pods with shell, number of seeds per pod, number of seeds per plant, seed weight per plant, 100 seed weight and yield kg / has. The study of the soil was carried out: analysis of fertility with disturbed sign, speed basic infiltration, moisture before and after watering for each method of irrigation with samples not disturbed. The coefficient of uniformity and efficiency of application was subsequently obtained. Readings of evaporimeter tank-type and craft were taken daily. Costs were considered for the production costs of the cultivation of peanuts by method of irrigation of: pumping, material of main driving, irrigation material, and farming from the phase of preparation of the land until the harvest; After identified variable costs was obtained the rate of marginal return (TRM); and economic analysis of the investment is amortized to a cash flow for five years with two cycles per year. As for the rustic tank was chosen by selecting a container with accessibility in the study area. The application with drip irrigation efficiency was 90%, with furrow irrigation 30% and sprinkling 65%. The crop yield of peanut seeded irrigated by drip was 2946,82 kg/ha/cycle against the grooves that was 1.037,27 Kg/ha/cycle; While with sprinkler irrigation was 2.344,55 Kg/ha/cycle; obtaining a rate of marginal return (TRM) 21.02% for sprinkler irrigation and 16.18% for drip irrigation. The coefficient of correlation between readings of "A" tank and the craft was 0.97; while the adjustment coefficient is 0,985 for what this last value must be multiplied by the readings made in artisan tank to fit the evaporimeter tank-type. The application in drip irrigation efficiency had repercussions on the yield of peanut because to be a more frequent irrigation allows that the roots are in optimal conditions of humidity and therefore better aerated. However the rate of marginal return (SCT) of the sprinkler is greater in drip irrigation, due to that, in this last although it is true existed higher performance, likewise variable costs were higher.